AEROBIC EXERCISE ON BODY MASS INDEX (BMI) CHANGE IN PERSON WITH OVERWEIGHT AND OBESITY - Muriyati Muriyati; Patima Patima; A. Suswani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. Aerobic Gymnastics is one type of exercise that increases fatty acid oxidation so that can lose weight. The purpose of this study was to determine the effect of aerobic exercise on body mass index (BMI) changes in person with obesity. Methods. This study was a quasi-experimental study using a pre-post test design. Individuals with obesity / overweight do aerobic exercise for 3 times a week for 6 weeks. Before aerobic exercise, the body mass index (BMI) measured and then after aerobic exercise done reassess the Body Mass Index (BMI). The number of sample studied were 30 women aged between 17-22 years old.Results.The results showed that BMI scores before aerobic exercise intervention is average of 27.54 and the average BMI of the respondents after attending aerobics for 6 weeks was 26.65 with a probability value (p = 0.000) smaller than (p = 0.05), which means that there is effect of aerobic exercise with BMI change. Discussion. BMI levels have changed significantly after aerobic exercise for 6 weeks.Keywords: BMI, aerobic, obesity